PHILOSOPHY OF EDUCATION AND PROSPECTS OF PHILOSOPHY - I. I. Sulima (Вестник Мининского университета, 2017)
This article discusses the crisis of philosophy, the emergence of industry philosophies as a manifestation of the crisis of philosophy. Clarifies the meaning and purpose of philosophy. The crisis of philosophy is considered taking into account the fact that the philosophy of the culture, part of fundamental science. Based on this methodological premise, explores the philosophy of education, its meaning and purpose and its relation to the crisis of philosophy as a fundamental science. Examines the role of education in overcoming the crisis of philosophy and the role of philosophy in education for the prospects of philosophy. Conclusions about the relationship of the perspectives of philosophy and industry philosophies.